Pragmatics of social media - Hoffmann, Christian R.; Bublitz, Wolfram (Handbooks of pragmatics, 2017)
This handbook provides a comprehensive overview of the pragmatics of social media, i.e. of digitally mediated and Internet-based platforms which are interactively used to share and edit self- and other-generated textual and audio-visual messages. Its five parts offer state-of-the-art reviews and critical evaluations in the light of on-going developments: Part I The Nature of Social Media sets up the conceptual groundwork as it explores key concept such as social media, participation, privacy/publicness. Part II Social Media Platforms focuses on the pragmatics of single platforms such as YouTube, Facebook. Part III Social Media and Discourse covers the micro-and macro-level organization of social media discourse, while Part IV Social Media and Identity reveals the multifarious ways in which users collectively (re-)construct aspects of their identities. Part V Social Media and Functions/Speech Acts surveys pragmatic studies on speech act functions such as disagreeing, complimenting, requesting. Each contribution provides a state-of-the-art review together with a critical evaluation of the existing research.